The effect of random shocks on reciprocal behavior in dynamic principal-agent settings - Rudolf Kerschbamer; Regine Oexl (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2021)
Previous work has shown that unobservable random shocks on output have a detrimental effect on effort provision in short-term ('static') employment relationships. Given the prevalence of long-term ('dynamic') relationships in firms, we investigate whether the impact of shocks is similarly pronounced in gift-exchange relationships where the same principalagent pair interacts repeatedly. In dynamic relationships, shocks have a significantly less pronounced negative effect on the agent's effort provision than in static relationships. In an attempt to identify the drivers for our results we find that the combination of a repeatedgame effect and a noise-canceling effect is required to avoid the detrimental effects of unobservable random shocks on effort provision.
Keywords: C72; C91; D81; 330; Gift exchange; principal agent model; incomplete contracts; random shocks; reciprocity; laboratory experiments; long-term contracts